Piezoelectric poly(vinylidene fluoride) microstructure and poling state in active tissue engineering - Ribeiro, C. (2015)
Tissue engineering often rely on scaffolds for supporting cell differentiation and growth. Novel paradigms for tissue engineering include the need of active or smart scaffolds in order to properly regenerate specific tissues. In particular, as electrical and electromechanical clues are among the most relevant ones in determining tissue functionality in tissues such as muscle and bone, among others, electroactive materials and, in particular, piezoelectric ones, show strong potential for novel tissue engineering strategies, in particular taking also into account the existence of these phenomena within some specific tissues, indicating their requirement also during tissue regeneration. This referee reports on piezoelectric materials used for tissue engineering applications. The most used materials for tissue engineering strategies are reported together with the main achievements, challenges and future needs for research and actual therapies. This review provides thus a compilation of the most relevant results and strategies and a start point for novel research pathways in the most relevant and challenging open questions.